Elaboração e caracterização de produto fermentado do extrato hidrossolúvel de baru (dipteryx alata vogel) com banana verde potencialmente simbiótico - Coutinho, Gabriela Silva Mendes (2020)
Alternatives to dairy products with functional characteristics have stimulated the interest of consumers and food industries. In this context, the aims of this study were to develop fermented products from the aqueous extract of baru almond, to characterize physicochemical, technological and morphological properties of green banana starch (BS) and to evaluate the effect of its addition on physicochemical parameters (pH, acidity, soluble solids, firmness, syneresis and color) and acceptability of fermented products; as well as to evaluate the effect of green banana starch, green banana pulp flour (BPF) and green banana pulp and peel flour (BPPF) addition on nutritional and functional potential (proximal composition, resistant starch, total phenolics, antioxidant capacity, mineral, phenolics and fatty acid profile) of developed products and the viability of probiotic bacteria. Two completely randomized experimental designs were set up, the first with five treatments, which consisted of adding five concentrations of green banana starch (0, 1.5, 3, 4.5 and 6 g 100 g-1) to fermented products; and the second design with four treatments, based on the addition of 4.5 g 100 g-1 of three different ingredients (BS, BPF and BPPF) on fermented baru almond extract, including control sample (fermented product without any addition). Data were submitted to analysis of variance (ANOVA) and when F test was significant, data were submitted to Tukey test or polynomial regression, considering a 5% probability (p <0.05), as well as principal component analysis (PCA). BS showed advantageous physicochemical and technological ––aspects for its application in fermented baru almond extract, such as low tendency to retrograde (67.53 RVU) compared to others starch sources and gelatinization temperature of 73.37 ºC. Addition of BS changed all physicochemical and technological variables evaluated. There was an increase in firmness, soluble solids and a reduction in syneresis of fermented products, due to the increase in BS addition, especially at highest concentrations (4.5 and 6 g 100g-1). Fermented products which received 3 and 4.5 g 100g-1 of BS were well accepted by consumers, with no differentiation in preference. Based on results of the first experiment, fixed addition of 4.5 g 100g1 of BS was established and compared to the addition of BPF and BPPF in fermented baru almond product, using the same amount of ingredient. Incorporation of green banana influenced proximal composition, energetic value and resistant starch content of elaborated products, mainly addition of BPPF, which increased its fiber, protein and ash contents, as well as potassium, magnesium and zinc. In general, green banana ingredients promoted an increase on total phenolics and antioxidant capacity of products, highlighting, once again, BPPF. Catechin and ferulic acid were phenolic compounds that increased the most, despite banana by-product addition. Addition of BS, BPF and BPPF did not change lipid profile of products, exception for butyrate, which reduced compared to control sample. Fatty acid profile of fermented products, regardless additions, was predominantly composed by polyunsaturated fatty acids, especially conjugated linoleic acid (46%). Addition of BS, PPF and BPPF positively affected the viability of L. acidophilus, while viability of B. animalis was influenced only by the BPPF. Fermented products, with or without the addition of green banana, showed a minimum count of 106 UFC g-1 for L. acidophilus and B. animalis. Therefore, these products can be considered potential carriers of probiotics, in order to promote health benefits. BPPF was the ingredient that most positively impacted probiotics viability and nutritional and functional potential of fermented products. Therefore, we can conclude that fermented baru almond product has nutritional, functional and acceptance potential. It can be a good potential vehicle for probiotics when green banana is added, especially BPPF incorporation.